Death-in-life: Staging Trauma and Loss in Goliarda Sapienza’s Destino coatto - Bazzoni, Alberica (Quaderni d'Italianistica)

(untitled) (Iter Press, 2022)
This essay investigates the representation of traumatic loss in Goliarda Sapienza’s Destino coatto, a collection of short narrative fragments published posthumously in 2002. I explore these texts by focusing on the original representation they offer of temporality in relation to trauma and loss, refracting a condition of death-in-life into temporal and spatial images. In particular, the night, accompanied by images of immobility and enclosed spaces, is a key signifier that represents a protective shield from the destructive force of life. Reflecting the liminal state of a subject in crisis, several texts are set on the threshold between day and night, and between indoor and outdoor spaces. Against the endless re-enactment of trauma, Sapienza stages a quest for immobility, a state of death-in-life that at the same time rejects and protects life.